EFFECTIVENESS OF EXTENSION ACTIVITIES ON FISH FARMERS GROUP IN THE NAGARI SUNGAI ANTUAN DISTRICT OF MUNGKA SUBDISTRICT LIMAPULUH KOTA WEST SUMATRA PROVINCE - Wanti, Desselvy; Nugroho, Firman; ', Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in September 2014 which took place in Nagari Sungai Antuan District of Mungka subdistrict Limapuluh kota West Sumatra province. The population is fish farmers as much as 20 people, and 1 extension. So the method of sample collections using the census method.Extension officers visit the fish farmers in the Nagari Sungai Antuan carried out 3-4 times a month, according to the needs of fish farmers. Of the three elements of behaviour change can be seen that fisheries extension activities in the Nagari Sungai Antuan in groups of fish farming in ponds has been effective. It can be seen from each element of behaviour change, the element of "knowledge" in the fish farmers ponds had been at the level of “analyzing” there are 15 people (75%) and the level of “integrate” there are 2 people (10%), fisheries extension in the Nagari Sungai Antuan has reached the stage of 85% effective. On the element of “attitude” fish farmers already on the level of “judge” there are 12 peope (60%) and at the level of “organize” as much as 5 people (15%), fisheries extension workers in the Nagari Sungai Antuan has reached the stage of 75% effective. On the element of “skill” they‟re level of “familiar” there are 12 people (60%) and the level of “skilled” there are 2 people (10%) and the level of “adaptation” as much as 2 people (10%) fisheries extension workers in the Nagari Sungai Antuan has reached the stage of 80% effective. It can be concluded fisheries extentension activities in the Nagari Sungai Antuan on each extension element has reached expectations.Keywords : The effectiveness of counseling, fish farmer rroup in swimming